Factors contributing to sex differences in functional outcomes and participation after stroke. (29th May 2018) - Phan, Hoang T.; Blizzard, Christopher L.; Reeves, Mathew J.; Thrift, Amanda G.; Cadilhac, Dominique A.; Sturm, Jonathan; Heeley, Emma; Otahal, Petr; Vemmos, Konstantinos; Anderson, Craig; Parmar, Priya; Krishnamurthi, Rita; et al.
Abstract : Objective: To examine factors contributing to the sex differences in functional outcomes and participation restriction after stroke. Methods: Individual participant data on long-term functional outcome or participation restriction (i.e., handicap) were obtained from 11 stroke incidence studies (1993–2014). Multivariable log-binomial regression was used to estimate the female:male relative risk (RR) of poor functional outcome (modified Rankin Scale score >2 or Barthel Index score <20) at 1 year (10 studies, n = 4, 852) and 5 years (7 studies, n = 2, 226). Multivariable linear regression was used to compare the mean difference (MD) in participation restriction by use of the London Handicap Scale (range 0–100 with lower scores indicating poorer outcome) for women compared to men at 5 years (2 studies, n = 617). For each outcome, study-specific estimates adjusted for confounding factors (e.g., sociodemographics, stroke-related factors) were combined with the use of random-effects meta-analysis. Results: In unadjusted analyses, women experienced worse functional outcomes after stroke than men (1 year: pooled RRunadjusted 1.32, 95% confidence interval [CI] 1.18–1.48; 5 years: RRunadjusted 1.31, 95% CI 1.16–1.47). However, this difference was greatly attenuated after adjustment for age, prestroke dependency, and stroke severity (1 year: RRadjusted 1.08, 95% CI 0.97–1.20; 5 years: RRadjusted 1.05, 95% CI 0.94–1.18). Women also had greater participation restriction than men (pooled MDunadjusted −5.55, 95% CI −8.47 to −2.63), but this difference was again attenuated after adjustment for the aforementioned factors (MDadjusted −2.48, 95% CI −4.99 to 0.03). Conclusions: Worse outcomes after stroke among women were explained mostly by age, stroke severity, and prestroke dependency, suggesting these potential targets to improve the outcomes after stroke in women.